Inbound open innovation and firm performance - Federico Moretti; Daniele Biancardi (Journal of Innovation & Knowledge (JIK), 2020)
A number of studies focus on the effects of open innovation on firm performance. However, in our view, previous contributions suffer from two main limitations: at first, there is still no homogeneity in the proposition of what "firm performance" is, according to extant literature. In addition, we see a heterogeneity of implications for the relationship between openness and performance, since there is still no consensus among authors on whether the relationship between openness and firm performance is positive, negative or non-linear. We address this issue through an empirical analysis of a cross-national unbalanced panel data of European firms listed in the five major European markets in the years 2008-2013. We seek to sort the impact of the level of inbound openness, derived by the amount invested in internal development versus the external acquisition of intangible assets on firm performance according to three dimensions: economic performance, measured as the amount of firm turnover; firm financial performance, measured with shares value; and human resources performance, measured as the level of employment. Results of panel data regression show that the effects of both internal development and external acquisition are positive and significant across different dimensions, but their output varies in terms in magnitude and distribution both variables are positively and significantly correlated with firm turnover, and that their effect on the latter is almost equal. In addition, we find that only internal development is positively and significantly correlated with the other two dimensions of performance, once we control for firm-specific time trends. Once we control for relative size of firms in the sample, we see that the effect of openness is more spread out across different class sizes, while the effect of internal development of intangibles influences the economic performance only for larger firms, and increases employment only for relatively smaller firms, while it has no effect on the financial side of performance.
Keywords: O32; O39; 650; Inbound; Open innovation; Outside-in; Performance